2001
DOI: 10.1115/1.1385833
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear PSE for Stability Analysis of the Blasius Boundary Layer Using Compact Scheme

Abstract: A highly accurate finite-difference PSE code has been developed to investigate the stability analysis of incompressible boundary layers over a flat plate. The PSE equations are derived in terms of primitive variables and are solved numerically by using compact method. In these formulations, both nonparallel as well as nonlinear effects are accounted for. The validity of present numerical scheme is demonstrated using spatial simulations of two cases; two-dimensional (linear and nonlinear) Tollmien-Schlichting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
4
8
1
Order By: Relevance
“…The comparison [4] of resulting neutral curves showed better agreement between results from linear PSE (LPSE) method and experiment [5−8] , as well as with and Gaster's results [1] . The nonlinear PSE (NPSE) [4,9] method also yielded results indicated good agreement with those obtained by DNS, including the amplitudes and shapes of the profiles of fundamental disturbance, higher harmonics, as well as mean flow distortion. Consequently, it has been used for further study of the stability problems of incompressible [10] boundary layers.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The comparison [4] of resulting neutral curves showed better agreement between results from linear PSE (LPSE) method and experiment [5−8] , as well as with and Gaster's results [1] . The nonlinear PSE (NPSE) [4,9] method also yielded results indicated good agreement with those obtained by DNS, including the amplitudes and shapes of the profiles of fundamental disturbance, higher harmonics, as well as mean flow distortion. Consequently, it has been used for further study of the stability problems of incompressible [10] boundary layers.…”
Section: Introductionsupporting
confidence: 65%
“…(9) are expressed as follows, where τ = u /T is a function of temperature in basic flow, P r is Prandtle number, P r = c * p μ * e /k * e , and γ is the ratio of specific heats. …”
Section: Appendixmentioning
confidence: 99%
“…Amplitudes were measured at Á = 1:3. This ÿgure indicates that the results of the SCFDM agree well with those of the fourth-order compact [17] (not shown here) and experimental data, when k = 1:01 is used. For k = 1:15, a numerical error is generated from the ÿrst steps of computation as shown in the ÿgure.…”
Section: Resultssupporting
confidence: 81%
“…Figure 16 presents the variations of non-dimensional skin friction coe cient versus Reynolds number for the subharmonic breakdown. The ÿgure also shows the comparison of the results with those obtained by the fourth-order compact method [17] to indicate the accuracy of the computation. As it can be seen for k = 1:15 used in the SCFDM, the numerical errors initiated from the ÿrst steps of computation, a ect the rise of the skin friction coe cient.…”
Section: Resultsmentioning
confidence: 97%
“…Joslin et al [6] showed that the PSE could exactly predict the evolution of two-dimensional (2D) TollmienSchlichting (T-S) waves and the transition of subharmonic instability waves and oblique waves. Esfahanian et al [7] used the PSE method to do the stability analysis and predict the transition position for the incompressible flat plate. The disturbances imposed at the entrance were consisted of one 2D wave and a pair of three-dimensional (3D) waves.…”
Section: Introductionmentioning
confidence: 99%